2020
DOI: 10.5109/4150509
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation On The Spiral Pipe Performance For Particle-Laden Liquids

Abstract: Newtonian and non-Newtonian fluids are commonly transported with the piping system, but non-Newtonian fluids with particle-laden are more complicated to be transported due to various factors. A deposition is one of the problems that must be investigated due to affecting flow efficiency. The purpose of this study is to investigate the performance of 3-lobes spiral pipe in relationship with particles effect. The working fluid used had several variations of concentration weight (i.e. Cw 20%, 30% and 40%). Test pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It was concluded that a lower pore density foam like 10 PPI caused only a low-pressure drop effect. However, particle laden fluids may affect flow efficiency 11) , and a fluctuation of pressure drop occurred even with the low pore density foam under this condition 12) . Since flow regimes also play an important role in influencing the pressure drop performance 13) , the exact model for the partially filled configuration is quite difficult to be formulated.…”
Section: Introductionmentioning
confidence: 94%
“…It was concluded that a lower pore density foam like 10 PPI caused only a low-pressure drop effect. However, particle laden fluids may affect flow efficiency 11) , and a fluctuation of pressure drop occurred even with the low pore density foam under this condition 12) . Since flow regimes also play an important role in influencing the pressure drop performance 13) , the exact model for the partially filled configuration is quite difficult to be formulated.…”
Section: Introductionmentioning
confidence: 94%
“…7) The inclusion of embedded sensors in the probe head has eliminated this inconvenience, resulting in erratic pressure measurements 8) .In combustion chambers, swirling jets are employed to regulate flames 9) . The presence of a swirl causes the formation of radial and axial pressure gradients, which influence flow fields 10) . To navigate safely and successfully in the air, air vehicles require correct air data information 11) .…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work has been done by investigator in past on spiral tube, nano fluids, still there is a huge scope in this area because invention of new advance particles and its involvement in new applications are increasing day by day. Some investigators performed work on particle-laden fluids (PLF) in spiral tube for thermal enhancement 37) . Some researches investigate the effect for screw pitch & nano particle mass fraction with spiral tube.…”
Section: Introductionmentioning
confidence: 99%